2014
DOI: 10.1021/nl500894h
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Doping of Carbon Nanotubes with Metallocenes for Application in Hybrid Carbon Nanotube/Si Solar Cells

Abstract: There is considerable interest in the controlled p-type and n-type doping of carbon nanotubes (CNT) for use in a range of important electronics applications, including the development of hybrid CNT/silicon (Si) photovoltaic devices. Here, we demonstrate that easy to handle metallocenes and related complexes can be used to both p-type and n-type dope single-walled carbon nanotube (SWNT) thin films, using a simple spin coating process. We report n-SWNT/p-Si photovoltaic devices that are >450 times more efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 40 publications
0
50
0
Order By: Relevance
“…[15,16] Pristine SWNTst ypicallys how p-type characteristics, [17] and their n-type counterparts have been prepared by reactingt hem with electron donor compounds via solutionm ixing, casting and vapor deposition in inert atmosphere.H owever,i ti sw ell-recognized that most n-type SWNTsa nd efficient n-type doping reagents such as alkali metals and amines are generally unstablei na ir, preventing the fabricationa ir-stable bipolar electronic devices and modules. [18][19][20][21] Nakashimae ta l. have recently reported the encapsulationo fatypical n-type molecular dopant,c obaltocene, into SWNTs, whichsubsequently showed air stability relatively higher than the correspondings imple mixture. [21] For further practical use, it is important to stabilizea ll the components including n-type SWNTsa nd n-type dopants after doping, that is, positively-charged species.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] Pristine SWNTst ypicallys how p-type characteristics, [17] and their n-type counterparts have been prepared by reactingt hem with electron donor compounds via solutionm ixing, casting and vapor deposition in inert atmosphere.H owever,i ti sw ell-recognized that most n-type SWNTsa nd efficient n-type doping reagents such as alkali metals and amines are generally unstablei na ir, preventing the fabricationa ir-stable bipolar electronic devices and modules. [18][19][20][21] Nakashimae ta l. have recently reported the encapsulationo fatypical n-type molecular dopant,c obaltocene, into SWNTs, whichsubsequently showed air stability relatively higher than the correspondings imple mixture. [21] For further practical use, it is important to stabilizea ll the components including n-type SWNTsa nd n-type dopants after doping, that is, positively-charged species.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes with cylinder-like, one-dimensional structures have attracted much interest for photovoltaic applications because of their electronic and optical properties [8][9][10][11] , including the ability to tune their band gaps over a wide wavelength range 12 , high carrier mobilities along their one-dimensional axes 13,14 and high optical transparency values with low resistivity 15 . Indeed, a variety of photovoltaic devices using carbon nanotubes such as carbon nanotube-based organic solar cells 16 , photoelectrochemical cells 17 , dye-sensitized solar cells 18 and carbon nanotube/Si solar cells 19,20 have been reported. Furthermore, the importance of carbon nanotubes as photovoltaic materials is continually increasing.…”
mentioning
confidence: 99%
“…Remarkably, these findings suggest that SWNT/Si hybrid solar cells could reach the PCE of Si p–n junction solar cells through optimized assembly of the interface . We have also shown that the analog system, n‐type SWNT thin films with bulk p‐type Si wafers, can approach the same efficiencies using small molecules or processes that ensure that O 2 is successfully removed from the SWNTs . Potential advantages of these hybrid approaches include the precise thickness control of the SWNT thin films and the room‐temperature fabrication of p–n junctions at the SWNT/Si interface .…”
Section: Introductionmentioning
confidence: 75%